Pengaruh Berat Katalis Dan Perlakuan Aktivasi Katalis Lempung Terhadap Pembuatan Biodiesel Dari Minyak Nyamplung - Fathiyah Zulfahni; Syaiful Bahri; Wisrayetti Wisrayetti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
This study aims to produce biodiesel from callophylum oil by using heterogeneous clay catalyst from Palas village. Characteristic of clay catalyst for biodiesel synthesis that will be analyzed in this research such as Si/Al ratio, surface area and pore size. Clay catalyst is made by grinding the clay until its size -100 +200 mesh. Clay was activated using H2SO4 solution with variation of the concentration 0,5 N, 1 N and 2 N. The mixture is filtered using a vacuum pump and calcined at 300 ºC for 3 hours. The producing of biodiesel through two stages: esterification and transesterification. In transesterification, clay catalyst is used having variation of catalyst weight was 0,1%, 0,5% and 1%, sample of oil 50 gram and ratio oil and methanol 1:9. The reaction lasted for 60 minutes at 60 ºC. The largest biodiesel yield on the use of 1% clay catalyst with variation of acid 1 N i.e. 89,50%. Characteristics of catalyst has a high Si/Al and a surface area ratio respectively 25,74 and 37,641 m2/gr, and pores are scattered on the surface. Biodiesel produced in accordance with predefined standards (SNI 7128:2015).Keywords: biodiesel, callophylum oil, Palas clay, transesterification.